Sensitivity of orographic precipitation enhancement to horizontal resolution in the operational Met Office Weather forecasts. (27th November 2012) - Smith, S. A.; Vosper, S. B.; Field, P. R.
Abstract Rain gauge observations show that when averaged over a large number of cases of frontal systems passing over the UK, strong orographic rain enhancement occurs on the lee slopes of the first hills encountered by the southwesterly flow in the warm sector. The operational forecasts using 1.5 km grid spacing produced realistic looking mean rainfall patterns over the Lake District and Wales, with an area‐averaged rain accumulation error of less than 2%. Model‐level rain rates increase with decreasing altitude consistent with the seeder‐feeder mechanism. Increasing the horizontal grid spacing in the operational weather forecast model decreases the amount of rain produced over the hills, thereby reducing forecast accuracy. The area‐averaged rain accumulations are 11–24% smaller than observed at 12 km grid spacing and 33–48% smaller than observed at 40 km grid spacing. In additional simulations of the 15 January 2011 case over the Lake District at 1.5 km grid spacing, replacing the orography with that used by the 12 and 40 km models reduced the area‐averaged rain accumulations by 10 and 23% respectively. These changes were due to reduced cloud water and ice mixing ratios over the lower hills resulting in slower increases in rain rate with decreasing altitude. It is demonstrated that neglecting the horizontal advection of falling rain drops results in too much rain falling on the windward slope and not enough falling on the lee slopes. Copyright © 2012 British Crown Copyright, the Met Office. Published by John Wiley & Sons Ltd.